Model Mengajar Pendidik Anak Usia Dini Pada RA Bait Qur’any At-Tafkir Tangerang Selatan - Akhmad Shunhaji; Ahmad Zain Sarnoto; Ely Budiyanti (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2019)
The results found in this thesis are early childhood education in RA Bait Qur’any at-Tafkir using a home learning teaching model. The intended home learning teaching model has characteristics. First; Islamic values. Second, there are 4 teaching models in RA at-Tafkir namely: Scientific, Muhadatsah, contextual learning and problem solving learning. The teaching model is integrated with Islamic values as the main basis. Third, the application has been done with home learning. The application involves the role and function of parents to run the RA at-Tafkir program.The results of this research have similarities with the opinions of Nurul Hikmah & Nurul Habiburrahmanuddin (2018) regarding education in the Qur'an being taught to children from an early age and Amirullah Syarbini (2017) who emphasizes character education in the family to instill Islamic values early on. This is different from the opinion of Maria Montesorri (1952), Syamsidah (2012), Timothy D. Walker (2017), Vidya Dwina paramita (2018) which gives children freedom to do daily activities and agendas. This study uses a qualitative descriptive approach with primary data sources. The data collection is done through document studies. The data is carried out deepening and confirmation through interviews and observations.